2005
DOI: 10.1111/j.1539-6924.2005.00598.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictive Genetic Testing for Alzheimer's Disease: Impact upon Risk Perception

Abstract: lifetime risk estimates of AD based on the same risk factors excluding APOE genotype. Perceptions of personal risk (PPR) for AD were assessed six weeks after risk assessments. PPR were correlated with actual lifetime risk estimates (r = 0.501; p < 0.0001). After controlling for lifetime risks communicated to participants, age, and number of affected relatives, PPR scores among those with an epsilon4-positive test result (the test result associated with increased AD susceptibility) (adjusted mean: 3.4 (SD: 0.7)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 23 publications
1
41
0
Order By: Relevance
“…32 There are other examples of psychological benefits accruing from negative biomarker test results such as testing for genetic susceptibility for cancer 33 or Alzheimer disease. 34 In other situations, biomarkers may serve as research tools by providing insights into disease mechanisms.…”
Section: Characteristics Of An Ideal Biomarkermentioning
confidence: 99%
“…32 There are other examples of psychological benefits accruing from negative biomarker test results such as testing for genetic susceptibility for cancer 33 or Alzheimer disease. 34 In other situations, biomarkers may serve as research tools by providing insights into disease mechanisms.…”
Section: Characteristics Of An Ideal Biomarkermentioning
confidence: 99%
“…No studies were found that assessed risk perceptions following genetic testing for dominantly inherited AD, while five studies were identified that described risk perceptions following APOE testing (LaRusse et al, 2005;Marteau et al, 2005;LaRusse Eckert et al, 2006;Hiraki et al, 2009;Linnenbringer et al, 2010).…”
Section: Impact Of Genetic Testing On Risk Perceptionmentioning
confidence: 99%
“…[5][6][7] These benefi ts might explain why so many adults tend to underestimate their personal risk of experiencing a CVD event. [8][9][10][11][12] Given the rapid emergence of genetic technologies that are likely to shape risk perceptions, 13 it is both timely and essential to investigate the long-term health impact of self-rated risk. We conducted a 15-year morRobert Gramling, MD …”
mentioning
confidence: 99%